Banster Method Accelerates Physical Ability Development in Collegiate Futsal Players: Metode Banster Mempercepat Pengembangan Kemampuan Fisik Pemain Futsal Perguruan Tinggi - Muhajer Sami Hassan (Academia Open, 2025)
General Background: Enhancing physical abilities through systematic training methods is crucial in sports science, particularly in futsal. Specific Background: The Banster method, a structured training approach, has been hypothesized to significantly improve athletes' physical performance. Knowledge Gap: Limited empirical studies have examined its effectiveness in collegiate futsal training, necessitating further investigation. Aims: This study evaluates the impact of the Banster method on developing physical abilities among collegiate futsal players. Results: A total of 15 players were selected, with five undergoing an exploratory experiment. Pre- and post-tests were conducted following a structured training regimen of 24 sessions over two months. Statistical analysis using SPSS (v23) confirmed that the Banster method led to significant improvements in explosive power, endurance, and speed, achieving 100% effectiveness in the experimental group. Novelty: This study provides empirical evidence supporting the Banster method’s superior efficiency in enhancing physical abilities compared to conventional training techniques. Implications: The findings suggest that integrating the Banster method into futsal training programs can optimize performance and accelerate skill development. Future research should explore its application across different sports disciplines and athlete levels to further validate its effectiveness. Highlights: Enhanced Performance: Improves power, endurance, and speed effectively. Proven Method: Statistical analysis confirms superior results. Wider Application: Usable across multiple sports disciplines. Keywords: Banster method, futsal training, physical abilities, sports performance, experimental study